Middle‐Range Theories of Institutional Change1. Issue 4 (15th October 2018) - Nee, Victor
Abstract : This article is based on my presidential address delivered in Baltimore at the 2018 annual meeting of the Eastern Sociological Society. In it, I explore the ways in which theories of the middle‐range help us advance sociology as a social science at a time when many express concern about the fragmentation of the discipline.